ASUHAN KEPERAWATAN HIPERTERMIA PADA An.F DENGAN DENGUE HEMORRHAGIC FEVER DAN PENERAPAN KOMPRES DENGAN ALOEVERA DIRUANG GARDENIA RSUD BINTAN TAHUN 2024 - Susanti, Seli; Sari , Komala; Yama , Erwi Marita; Arianingsih , Tri (Seroja Husada: Jurnal Kesehatan Masyarakat, 2025)
DHF is a vector-based disease that is the leading cause of death in many tropical countries. DHF is endemic, often attacks the community in the form of epidemics and is accompanied by a fairly high mortality rate, especially in those under 15 years of age. The presence of the virus in the blood will stimulate the temperature control center in the hypothalamus, which then causes hyperthermia. Management of DHF children with hyperthermia can be carried out with non-pharmacological treatment, namely aloe vera compresses. Aloe vera compresses are a physical method to reduce fever that can be done when a child has a high fever. The aloe vera plant contains saponins which are beneficial when lowering body temperature. This is because aloe vera has a water content of 95%. The purpose of writing this Final Scientific Paper for Nursing is to apply nursing care to An.F with Dengue Hemorrhagic Fever and the application of compresses with aloe vera. The method of writing this scientific paper uses descriptive qualitative, namely with the case study method or approach. The implementation of this nursing care was carried out from September 30 to October 3, 2024. The results of giving aloe vera compresses for 3 days can reduce hyperthermia in children with DHF from a temperature of39.20C-370C.Conclusion: Using aloe vera compresses is an effective way to lower body temperature non-pharmacologically using the heat transfer method through conduction and evaporation.